Sophia Parnok : the Life and Work of Russia's Sappho. - Burgin, Diana L. (Cutting Edge: Lesbian Life and Literature Series., 1994)
The weather in Moscow is good, there's no cholera, there's also no lesbian love ... Brrr! Remembering those persons of whom you write me makes me nauseous as if I'd eaten a rotten sardine. Moscow doesn't have them--and that's marvellous."--Anton Chekhov, writing to his publisher in 1895. Chekhov's barbed comment suggests the climate in which Sophia Parnok was writing, and is an added testament to to the strength and confidence with which she pursued both her personal and artistic life. Author of five volumes of poetry, and lover of Marina Tsvetaeva, Sophia Parnok was the only openly lesb.